Systematic Literature Review: Implementasi Rational Emotive Behavior Therapy (REBT) untuk Mengatasi Permasalahan Psikologis Siswa di Lingkungan Pendidikan - Ningsih, Fitria; Purwoko, Budi; Al Habsy, Bakhrudin (Universitas Muhammadiyah Metro, 2025)
This study aims to see how effective the implementation of Rational Emotive Behavior Therapy (REBT) is in overcoming psychological problems in the educational environment. This study uses the Systematic Literature Review (SLR) method which analyzes as many as 20 scientific articles published within a period of 10 years, 2015-2024. The results of this study show that the REBT approach is consistently effective in dealing with various psychological problems of students, such as bullying, low learning motivation, academic anxiety, and other psychological problems. The techniques used in the analysis of this research are cognitive disputing, self talk, and reframing. However, there are still challenges in the implementation of REBT, such as the readiness of counselors and limited training. That way, increasing the capacity of BK teachers and integrating REBT in the provision of BK services is crucial. In this study, it has provided a theoretical and practical basis for the development of evidence-based psychological interventions in the educational environment.